Alien inhibits E2F1 gene expression and cell proliferation - Kob, Robert; Baniahmad, Aria; Escher, Niko; Von Eggeling, Ferdinand; et al. (Biochimica Et Biophysica Acta-Molecular Cell Research, 2007)
Recently, using a proteomic approach we have identified the corepressor Alien as a novel interacting factor of the cell cycle regulator E2F1. Unclear was whether this interaction influences cell proliferation and endogenous E2F1 target gene expression. Here, we show by chromatin immunoprecipitation (Ch1P) that Alien is recruited in vivo to the E2F binding sites present in the E2F1 gene promoter, inhibits the transactivation of E2F1 and represses endogenous E2F1 gene expression. Interestingly, using synchronized cells to assess the expression of Alien profile during cell cycle the levels of endogenous Alien are increased during G1, G1/S and G2 phase. Furthermore, stable transfection of Alien leads to reduction of cell proliferation. Thus, the data suggest that Alien acts as a corepressor for E2F1 and is involved in cell cycle regulation. (C) 2007 Elsevier B.V. All rights reserve
Keywords: corepressor; gene repression; transcription; E2F1; cell cycle